Mammographic Screening at Age 40 or 45? What Difference Does it Make? the Potential Impact of American Cancer Society Mammography Screening Guidelines. Issue 8 (August 2017) - Fancher, Crystal E.; Scott, Anthony; Allen, Ahkeel; Dale, Paul
This is a 10-year retrospective chart review evaluating the potential impact of the most recent American Cancer Society mammography screening guidelines which excludes female patients aged 40 to 44 years from routine annual screening mammography. Instead they recommend screening mammography starting at age 45 with the option to begin screening earlier if the patient desires. The institutional cancer registry was systematically searched to identify all women aged 40 to 44 years treated for breast cancer over a 10-year period. These women were separated into two cohorts: screening mammography detected cancer (SMDC) and nonscreening mammography detected cancer (NSMDC). Statistical analysis of the cohorts was performed for lymph node status (SLN), five-year disease-free survival, and five-year overall survival. Women with SMDC had a significantly lower incidence of SLN positive cancer than the NSMDC group, 9 of 63 (14.3%) versus 36 of 81 (44 %; P < 0.001). The five-year disease-free survival for both groups was 84 per cent for SMDC and 80 per cent for NSMDC; this was not statistically significant. The five-year overall survival was statistically significant at 94 per cent for the SMDC group and 80 per cent for the NSMDC group (P < 0.05). This review demonstrates the significance of mammographic screening for early detection and treatment of breast cancer. Mammographic screening in women aged 40 to 44 detected tumors with fewer nodal metastases, resulting in improved survival and reaffirming the need for annual mammographic screening in this age group.